The World of the New Testament : Cultural, Social, and Historical Contexts - Green, Joel B., 1956-; McDonald, Lee Martin, 1942- (grand rapids, michigan baker academic, 2013)
"A team of distinguished specialists introduces the Jewish, Hellenistic, and Roman backgrounds necessary for understanding the New Testament and the early church"--Publisher's summary.
Includes bibliographical references and index.
Keywords: Bible. -- History of biblical events; Bible. -- Criticism, interpretation, etc; Jews -- History -- 586 B.C.-70 A.D.; Jews -- Palestine -- Social life and customs -- To 70 A.D.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Civilization, Greco-Roman -- Social aspects; Church history -- Primitive and early church, ca. 30-600.; Palestine -- History -- To 70 A.D.; Greece -- History -- 146 B.C.-323 A.D.; Rome -- History -- Empire, 30 B.C.-476 A.D.